Determinants of Factors Causing Unwanted Pregnancy in Adolescents: A Literature Review - Dewa Ayu Dewi Permata Sari; Diah Indriani (Universitas Airlangga, 2021)
ABSTRACTBackground: The Phenomenon of unwanted pregnancy among adolescents is still rife in Indonesia. Results of interviews with the head of the National Population and Family Planning Agency (BKKBN), Hasto Wardoyo, explained in 2020 that there are not enough unwanted pregnancies in Indonesia which reach 17.5%.Objectives: Provide an overview of the determinants of unwanted pregnancy in adolescents in Indonesia.Methods: An article search was conducted using Google Scholar and Garuda Portal with the keywords